1998
DOI: 10.1111/j.1467-8624.1998.tb06161.x
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Sensitivity and Children's Interpersonal Difficulties

Abstract: Some children respond to social rejection in ways that undermine their relationships, whereas others respond with more equanimity. This article reports 3 studies that test the proposition that rejection sensitivity-the disposition to defensively (i.e., anxiously or angrily) expect, readily perceive, and overreact to social rejectionhelps explain individual differences in response to social rejection. Data were from urban, minority (primarily Hispanic and African American) fifth to seventh graders. Study 1 desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
328
3
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 339 publications
(361 citation statements)
references
References 31 publications
19
328
3
7
Order By: Relevance
“…For example, several studies have found that when adolescents and young adults are higher in RS they are more likely to react with aggression following the presentation of events that imply rejection (Ayduk et al 1999;Buckley et al 2004;Twenge et al 2001). Others have found similar results in young adolescents (Downey et al 1998b). In other studies, individuals had heightened tendency to withdraw from interactions following the presentation of events that implied rejection (Leary et al 1998;Williams 2001;Zimmer-Gembeck and Nesdale 2013).…”
Section: Rs Behavioralmentioning
confidence: 93%
See 4 more Smart Citations
“…For example, several studies have found that when adolescents and young adults are higher in RS they are more likely to react with aggression following the presentation of events that imply rejection (Ayduk et al 1999;Buckley et al 2004;Twenge et al 2001). Others have found similar results in young adolescents (Downey et al 1998b). In other studies, individuals had heightened tendency to withdraw from interactions following the presentation of events that implied rejection (Leary et al 1998;Williams 2001;Zimmer-Gembeck and Nesdale 2013).…”
Section: Rs Behavioralmentioning
confidence: 93%
“…RS theory (Downey and Feldman 1996;Downey et al 1998b) and previous research suggest that RS is associated with maladaptive behavioral responses to many social situations, as well as a range of emotional and behavioral problems, during adolescence and adulthood. However, the present longitudinal study was the first to consider anxious and angry forms of RS, and related processes, in order to simultaneously account for depressive symptoms and aggressive behavior.…”
Section: Study Aims and Hypothesesmentioning
confidence: 97%
See 3 more Smart Citations